Age‐Related Differences in Takotsubo Syndrome: Results From the Multicenter GEIST Registry - Ibrahim El‐Battrawy; Francesco Santoro; Iván J. Núñez‐Gil; Toni Pätz; Luca Arcari; Mohammad Abumayyaleh; Federico Guerra; Giuseppina Novo; Beatrice Musumeci; Luca Cacciotti; Enrica Mariano; Pasquale Caldarola; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The role of age in the short‐ and long‐term prognosis of takotsubo syndrome (TTS) is controversial. The aim of the present study was to evaluate age‐related differences and prognostic implications among patients with TTS. Methods and Results In total, 2492 consecutive patients with TTS enrolled in an international registry were stratified into 4 groups (<45, 45–64, 65–74, and ≥75 years). The median long‐term follow‐up was 480 days (interquartile range, 83–1510 days). The primary outcome was all‐cause mortality (in‐hospital and out‐of‐hospital mortality). The secondary end point was TTS‐related in‐hospital complications. Among the 2479 patients, 58 (2.3%) were aged <45 years, 625 (25.1%) were aged 45 to 64 years, 733 (29.4%) were aged 65 to 74 years, and 1063 (42.6%) were aged ≥75 years. Young patients (<45 years) had a higher prevalence of men (from youngest to oldest, 24.1% versus 12.6% versus 9.7% versus 11.4%; P<0.01), physical triggers (46.6% versus 27.5%, 33.9%, and 38.4%; P<0.01), and non‐apical forms of TTS (25.9% versus 23.7%, 12.7%, and 9%; P<0.01) than those aged 45 to 64, 65 to 74, and ≥75 years. During hospitalization, young patients experienced a higher rate of in‐hospital complications (32.8% versus 23.4%, 27.4%, and 31.9%; P=0.01), but in‐hospital mortality was higher in the older group (0%, 1.6%, 2.9%, and 5%; P=0.001). Long‐term all‐cause mortality was significantly higher in the older cohort (5.6%, 6.4%, 11.3%, and 22.3%; log‐rank P<0.001), as was long‐term cardiovascular mortality (0%, 0.9%, 1.9%, and 3.2%; log‐rank P=0.01). Conclusions Young patients with TTS have a typical phenotype characterized by a higher prevalence of male sex, non‐apical ballooning patterns, and in‐hospital complications. However, in‐hospital and long‐term mortality are significantly lower in young patients with TTS. Registration URL: https://classic.clinicaltrials.gov/ct2/show/NCT04361994. Unique identifier: NCT04361994.